2021
DOI: 10.35848/1347-4065/ac127c
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile operation of vertical ferroelectric gate-all-around nanowire transistors

Abstract: Ferroelectric gate-all-around (GAA) transistors with a nanowire (NW) channel standing vertically on the substrate would be a potential breakthrough to overcome limitations in the high-integration of ferroelectric memories. In the present study, we fabricated vertical ferroelectric GAA NW transistors (VFGAANWTs) with ZnO NWs (average diameters: 53-193 nm) as the channel, (Hf,Zr)O 2 film (average thicknesses: 9.3-58 nm) as the gate ferroelectric, and Ti as the gate electrode. The channel length was 100-300 nm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Adding ferroelectric material to the VNWFET gate stack [18] enables non-volatile logic as well as non-volatile reconfigurability. For example, a non-volatile full adder [19] is able to store one of the summands in a non-volatile manner, which is of particular interest in multiplication operations used in digital filters or convolutional neural networks, and where one summand varies constantly (data), while the other one varies rarely (coefficients).…”
Section: ) Ferro Gatementioning
confidence: 99%
“…Adding ferroelectric material to the VNWFET gate stack [18] enables non-volatile logic as well as non-volatile reconfigurability. For example, a non-volatile full adder [19] is able to store one of the summands in a non-volatile manner, which is of particular interest in multiplication operations used in digital filters or convolutional neural networks, and where one summand varies constantly (data), while the other one varies rarely (coefficients).…”
Section: ) Ferro Gatementioning
confidence: 99%
“…11,12) It has been reported that the polarization of a ferroelectric-gate insulator can be employed in oxide-channel-based FeFETs. [11][12][13][14][15][16][17][18][19][20][21] Such FETs are non-volatile and have superior transparency, making them attractive for application to transparent devices.…”
Section: Introductionmentioning
confidence: 99%